The association between lifestyle factors and mental well-being among dental students - Lim, Shea Lee; Abu Bakar, Noraini; Ahmad Basri, Nadzirah; Mohamed Ludin, Salizar (Penerbit Universiti Sains Malaysia, 2024)
Dentistry can be considered a challenging field, with dental students often experiencing high levels of stress and poor mental health. Hence, maintaining mental well-being is important so that dental students can cope with their stressors effectively. Lifestyle factors like physical activity, sleep problems, and addictions impact the levels of mental well-being. This article aimed to identify the association between dental students’ lifestyle factors and mental well-being. This cross-sectional descriptive study was conducted among all the undergraduate dental students at a university in Malaysia. Data were collected by using a self-administered questionnaire [which included questions on demographic background, lifestyle factors, and the Warwick-Edinburgh Mental Well-being Scale (WEMWBS)] and analysed using SPSS (version 26.0). Out of the surveyed students, 83.2% responded. The mean WEMWBS score for this study population was 46.09 ± 7.93. The results showed that engagement in physical activity positively affected mental well-being scores, while the presence of sleep-related problems was associated with lower mental well-being scores. Encouraging the adoption of healthier lifestyle factors, such as regular physical activity and practising good sleep hygiene along with the intervention of sleep-related problems, could improve mental well-being levels among dental students significantly.